Anti‐Müllerian hormone levels in salpingectomized compared with nonsalpingectomized women with tubal factor infertility and women with unexplained infertility. (4th October 2013) - Grynnerup, Anna G.‐A.; Lindhard, Anette; Sørensen, Steen
Abstract Objective To investigate the consequence of salpingectomy on ovarian reserve by measuring anti‐Müllerian hormone (AMH) levels before in vitro fertilization (IVF) treatment in salpingectomized women compared with nonsalpingectomized women with tubal factor infertility, women with unexplained infertility and fertile control women, and to evaluate whether AMH levels could predict IVF outcome. Design Cross‐sectional study extended from a previous prospective study. Setting Four university fertility clinics. Patients Seventy‐one women with infertility and 21 fertile controls. Interventions Blood sampling and IVF and embryo transfer in the following cycle. Main outcome measure Serum AMH levels and oocytes retrieved. Results Anti‐Müllerian hormone levels were significantly lower in the salpingectomy infertility group (median 16.1, range 5.2–54 pmol/L) compared with the nonsalpingectomy tubal factor infertility group (median 23.4, range 3.5–50 pmol/L; p = 0.04). In all groups, AMH levels correlated positively with the number of oocytes retrieved. AMH predicted poor response (five or fewer oocytes) with a sensitivity and specificity of 90% and 70%, at a 19 pmol/L cut‐off value. Conclusion Serum AMH levels were lower in salpingectomized women compared with women with tubal factor infertility and preserved Fallopian tubes, indicating that ovarian reserve might be affected by tubal surgery. Furthermore, serum AMH levels could predict a poor oocyte response (five or fewer oocytes) in the study group of infertile women.